A Novel Model of Cancer-Induced Peripheral Neuropathy and the Role of TRPA1 in Pain Transduction - Ahmad Maqboul; Bakheet Elsadek (Pain Research and Management)
Background. Models of cancer-induced neuropathy are designed by injecting cancer cells near the peripheral nerves. The interference of tissue-resident immune cells does not allow a direct contact with nerve fibres which affects the tumor microenvironment and the invasion process. Methods. Anaplastic tumor-1 (AT-1) cells were inoculated within the sciatic nerves (SNs) of male Copenhagen rats. Lumbar dorsal root ganglia (DRGs) and the SNs were collected on days 3, 7, 14, and 21. SN tissues were examined for morphological changes and DRG tissues for immunofluorescence, electrophoretic tendency, and mRNA quantification. Hypersensitivities to cold, mechanical, and thermal stimuli were determined. HC-030031, a selective TRPA1 antagonist, was used to treat cold allodynia. Results. Nociception thresholds were identified on day 6. Immunofluorescent micrographs showed overexpression of TRPA1 on days 7 and 14 and of CGRP on day 14 until day 21. Both TRPA1 and CGRP were coexpressed on the same cells. Immunoblots exhibited an increase in TRPA1 expression on day 14. TRPA1 mRNA underwent an increase on day 7 (normalized to 18S). Injection of HC-030031 transiently reversed the cold allodynia. Conclusion. A novel and a promising model of cancer-induced neuropathy was established, and the role of TRPA1 and CGRP in pain transduction was examined.